2020
DOI: 10.3390/cancers12123575
|View full text |Cite
|
Sign up to set email alerts
|

Physical Plasma-Treated Skin Cancer Cells Amplify Tumor Cytotoxicity of Human Natural Killer (NK) Cells

Abstract: Skin cancers have the highest prevalence of all human cancers, with the most lethal forms being squamous cell carcinoma and malignant melanoma. Besides the conventional local treatment approaches like surgery and radiotherapy, cold physical plasmas are emerging anticancer tools. Plasma technology is used as a therapeutic agent by generating reactive oxygen species (ROS). Evidence shows that inflammation and adaptive immunity are involved in cancer-reducing effects of plasma treatment, but the role of innate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…Along those lines, we have previously shown increased myeloid and lymphoid immuno-infiltration into gas plasma-treated syngeneic B16 melanomas in vivo [47], while checkpoint immunotherapy augmented therapeutic efficacy in the similar tumour model, but using another plasma device [48]. An in vitro study using the same two tumour cell lines showed that not only the adaptive immune system mediates anti-cancer effects after CAP treatment, but also innate immune cells, such as NK cells, lead to significantly higher apoptosis of tumour cells, due to expression modulation of activating and inhibiting receptors on tumour cells after CAP treatment [49].…”
Section: Discussionmentioning
confidence: 99%
“…Along those lines, we have previously shown increased myeloid and lymphoid immuno-infiltration into gas plasma-treated syngeneic B16 melanomas in vivo [47], while checkpoint immunotherapy augmented therapeutic efficacy in the similar tumour model, but using another plasma device [48]. An in vitro study using the same two tumour cell lines showed that not only the adaptive immune system mediates anti-cancer effects after CAP treatment, but also innate immune cells, such as NK cells, lead to significantly higher apoptosis of tumour cells, due to expression modulation of activating and inhibiting receptors on tumour cells after CAP treatment [49].…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of this cross-species approach is underlined by DC activation being triggered via the binding of immune-stimulatory molecules to evolutionarily conserved pattern recognition receptors such as toll-like receptors that only differ slightly in structure and subsequent signaling pathways across species 80,81 . Effects of plasma-derived species on myeloid cells such as DCs [82][83][84] , macrophages 85,86 as well as innate lymphocytes 87 was suggested before already.To gain evidence of the tumor treatment regimes' ability to induce DC maturation, we characterized the expression of reliable maturation www.nature.com/scientificreports/ markers on DCs. We found kINPen but not V jet plasma-treated tumor cells to promote dendritic cell maturation and tumor cell phagocytosis.…”
Section: Discussionmentioning
confidence: 80%
“…This may also affect other targets of the TME, such as thiols [ 57 , 58 , 59 ] and extracellular matrix hyaluron [ 60 ], that upon plasma treatment were recently identified to show disrupted binding to its receptor CD44 [ 61 ]. The second is long-term effects on the expression levels of immune-relevant ligands and receptors, as we and others have reported recently [ 54 , 62 , 63 , 64 , 65 , 66 ]. Importantly, both events may combine during gas plasma exposure of cancer tissue to promote antitumor immunity [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 91%